Claiming the dispossession : the politics of hi/storytelling in post-imperial Europe - Biti, Vladimir, 1952- (Balkan studies library, 2017)
"With the Treaty of Versailles, the Western nation-state powers introduced into the East Central European region the principle of national self-determination. This principle was buttressed by frustrated native elites who regarded the establishment of their respective nation-states as a welcome opportunity for their own affirmation. They desired sovereignty but were prevented from accomplishing it by their multiple dispossession. National elites started to blame each other for this humiliating condition. The successor states were dispossessed of power, territories, and glory. The new nation-states were frustrated by their devastating condition. The dispersed Jews were left without the imperial protection. This embarrassing state gave rise to collective (historical) and individual (fictional) narratives of dispossession. This volume investigates their intended and unintended interaction. Contributors are: Davor Beganović, Vladimir Biti, Zrinka Božić-Blanuša, Marko Juvan, Bernarda Katušić, Nataša Kovačević, Petr Kučera, Aleksandar Mijatović, Guido Snel, and Stijn Vervaet."--